Self-assembly studies on triazolepolycarbodiimide-g-polystyrene copolymers. (1st June 2016) - Kulikov, Oleg V.; Siriwardane, Dumindika A.; McCandless, Gregory T.; Mahmood, Samsuddin F.; Novak, Bruce M.
Abstract: We report here the formation of polycarbodiimide- g -polystyrene copolymer secondary structures, i.e. nano-rings, "craters", and spherical particles, resulted from dewetting phenomena that have been corroborated by combination of tapping mode AFM, SEM, DLS, and powder XRD techniques. These morphological findings represent certain interest in the area of novel functional materials. Well-defined ring-like aggregates are believed to be the transition motifs arising due to the concentration changes and, therefore, mainly seen when diluted CHCl3 stock solutions were used for AFM specimen preparation. Applying more polar THF or THF/EtOH (25% by volume) solvent systems influenced aggregation of grafted copolymers into spherical motifs with a particle size dependent on concentration that was also confirmed by dynamic light scattering (DLS) studies in solution. Characterization performed by electron microscopy techniques (SEM and TEM) provides evidence that AFM-observed morphologies do exist beyond the thin film phase and XRD findings are suggestive that non-covalent interactions of macromolecules play an important role in their self-organization in solid state. Graphical abstract: